Standard Atlas of Fillmore County Minnesota (Plat book) - George A. Ogle & Company, Publishers & Engravers (Fillmore County Historical Society, 1896)
Standard Atlas of Fillmore County Minnesota including a plat book of the villages, cities, townships, schools, churches, railroads, streams, roads, cemeteries of the county. Map of the State, United States, and World. Farmer's Directory, Reference Business Directory, and Departments devoted to general information. Analysis of the system of the U. S. land surveys, and digest of the system of civil government.